Possibility of accepting students of the Doctor of Public Administration program Faculty of Public Administration Shinawatra University - Khumsap, Ratthburut; Vitheesawat, Pinai; Nukulkij, Dheetawat (Journal of Nakhonratchasima college (Humanities and Social Sciences), 2024)
The objectives of this research article are: (1) To study and draw a summary of the results of the curriculum critique. By the field of public administration Faculty of Public Administration Shinawatra University In drafting the Doctor of Public Administration curriculum Under the curriculum development stage (2) To study the opinions of the general public, entrepreneurs, and professors of the Public Administration program. and university students pursuing the Doctor of Public Administration program. This is quantitative research. The population group is the general public, entrepreneurs, public administration professors. and university students by calculating the sample 380. The tool used is It’s a questionnaire. Statistics used in data analysis include percentages, averages. The results of the study found that Summary of the results of the curriculum critique, main course category 18 credits, elective course category 3 credits, foreign language course category. (Not counting credits) Dissertation (Dissertation) 36 credits Opinions towards the Doctor of Public Administration program of university students found that most of them receive news from Facebook (40 percent) and news from the university such as professors, activities at the university. 40 percent from colleges and from other channels Percentage 20Get to know the Doctor of Public Administration program Percentage 100 are interested in studying the Doctor of Public Administration program at a high level. accounting for 60 percent, followed by those interested in studying the Doctor of Public Administration program at the highest level Accounted for 40 percent